2017
DOI: 10.1039/c7ra08292d
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive morin sensor based on PEDT–Au/rGO nanocomposites modified glassy carbon electrode

Abstract: In this work, we fabricated a sensitive electrochemical sensor based on a PEDT-Au/reduced graphene oxide nanocomposites (PEDT-Au/rGO) modified glassy carbon electrode (PEDT-Au/rGO/GCE) for electrochemical determination of morin. A facile, effective and high-efficiency one-pot method was employed to synthesize the PEDT-Au/rGO nanocomposites. The morphology and structure of asprepared PEDT-Au/rGO nanocomposites were characterized by using a scanning electron microscope (SEM), transmission electron microscope (TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…This result suggests oxidation of morin to be an adsorption-controlled electrochemical process . On the basis of the Laviron formula shown in eq for an irreversible adsorption system, the number of electrons ( n ) transferred during the oxidation process can be calculated where F is Faraday’s constant, Q is equal to the peak area (0.0180971 m 2 ), ν is the scan rate (V/s), R is the gas constant (J/mol/K), and T is the experimental temperature (K). n was calculated to be around 2 indicating that two electrons were involved in the electron transfer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result suggests oxidation of morin to be an adsorption-controlled electrochemical process . On the basis of the Laviron formula shown in eq for an irreversible adsorption system, the number of electrons ( n ) transferred during the oxidation process can be calculated where F is Faraday’s constant, Q is equal to the peak area (0.0180971 m 2 ), ν is the scan rate (V/s), R is the gas constant (J/mol/K), and T is the experimental temperature (K). n was calculated to be around 2 indicating that two electrons were involved in the electron transfer.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests oxidation of morin to be an adsorptioncontrolled electrochemical process. 12 On the basis of the Laviron formula shown in eq 5 for an irreversible adsorption system, 52−54 the number of electrons (n) transferred during the oxidation process can be calculated 12…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine morin, a number of voltammetric sensors were proposed. These sensors are based on a glassy carbon electrode modified with carboxylated nanotubes; 9 a composite of graphene oxide, poly-3,4-ethylenedioxythiophene, and gold nanoparticles; 10 1-butyl-3-methylimidazoliumhexafluorophosphat and chitosan; 11 poly(tetrafluroethylene)-deoxyribonucleate acid; 12 and vanadium pentoxide. 13 Sensors developed based on a mixture of carbon nanotubes and paraffin oil, 14 renewable pencil electrodes 15 , and carbon fiber paper electrode modified with poly(2,5-dimercapto-1,3,4-thiadiazole) 16 were also proposed (comparative characteristics of the proposed sensors are presented in Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In previous studies, glassy carbon electrode-modied chemically active materials showed high sensitivity to organic substances. [4][5][6] Metal nanoparticle materials have attracted much research interest because of their good electrical conductivity and excellent catalytic properties, and electrochemical sensor-modied metal nanoparticles worked well in the determination of DNA, proteins, neurotransmitters, phytohormones and organic pollutants. [7][8][9][10] However, these metal nanoparticles are unstable due to their high activity, easy oxidation and easy agglomeration due to van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%